2020
DOI: 10.1021/acsnano.9b03978
|View full text |Cite
|
Sign up to set email alerts
|

Stromal Modulation and Treatment of Metastatic Pancreatic Cancer with Local Intraperitoneal Triple miRNA/siRNA Nanotherapy

Abstract: Nanomedicines achieve tumor-targeted delivery mainly through enhanced permeability and retention (EPR) effect following intravenous (IV) administration. Unfortunately, the EPR effect is severely compromised in pancreatic cancer due to hypovascularity and dense desmoplastic stroma. Intraperitoneal (IP) administration may be an effective EPR-independent local delivery approach to target peritoneal tumors. Besides improved delivery, effective combination delivery strategies are needed to improve pancreatic cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
111
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(115 citation statements)
references
References 73 publications
4
111
0
Order By: Relevance
“…Validating effective RNA treatment strategies in a number of cancer treatment studies [18][19][20][21][22][23][24] can also be used as an adjuvant treatment for DCM. In the future, we can construct a nanotargeted therapeutic system by designing miRNA overexpression vector gene drugs together with chemical drugs through rational encapsulation of nanomaterials such as cationic polymers and liposomes and connecting cardiac-targeting ligands in the outer layer [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Validating effective RNA treatment strategies in a number of cancer treatment studies [18][19][20][21][22][23][24] can also be used as an adjuvant treatment for DCM. In the future, we can construct a nanotargeted therapeutic system by designing miRNA overexpression vector gene drugs together with chemical drugs through rational encapsulation of nanomaterials such as cationic polymers and liposomes and connecting cardiac-targeting ligands in the outer layer [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…At this time point, the bio‐distribution analysis indicated that the intra‐tumor accumulation efficiency of COi6‐4Cl NPs was ≈8.0% ID g −1 (Figure S21, Supporting Information), which was a relatively good result among the similar passivate delivery system through the EPR effect. [ 18 ] Notably, the fluorescence signals at tumor sites after 48 h post injection were still high, which indicated that COi6‐4Cl could serve as a long‐term NIR‐II fluorescence imaging agent.…”
Section: Methodsmentioning
confidence: 99%
“…Tumor cells have barriers to protect them from the body's immune system, such as an impenetrable stroma and immunosuppressive cells in the tumor environment [60]. Tumor cells block antigen overexpression and increase regulatory-T cells and hence escape the immune system of the body.…”
Section: Application In Immunotherapymentioning
confidence: 99%